2019
DOI: 10.1124/jpet.119.260471
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine Reduces Vascular Dysfunction Associated with Hypertension by Attenuating Protein Kinase G/Vasodilator-Stimulated Phosphoprotein Signaling

Abstract: Vascular dysfunction associated with hypertension comprises hypercontractility and impaired vasodilation. We have previously demonstrated that triiodothyronine (T3), the active form of thyroid hormone, has vasodilatory effects acting through rapid onset mechanisms. In the present study, we examined whether T3 mitigates vascular dysfunction associated with hypertension. To test the direct effects of T3 in hypertensive vessels, aortas from female Dahl salt-sensitive (Dahl SS) rats fed a high-salt diet (8% NaCl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
(47 reference statements)
1
9
0
3
Order By: Relevance
“…Experimental studies indicate that administration of TH after acute myocardial infarction (AMI) may improve myocardial function by reducing the infarct size [ 17 ]. T3 can mitigate hypertension-related vascular dysfunction via its antioxidant effect [ 16 , 24 ]. However, further research is needed before TH can be therapeutically administered to patients who have had MI or patients with hypertension [ 18 ].…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…Experimental studies indicate that administration of TH after acute myocardial infarction (AMI) may improve myocardial function by reducing the infarct size [ 17 ]. T3 can mitigate hypertension-related vascular dysfunction via its antioxidant effect [ 16 , 24 ]. However, further research is needed before TH can be therapeutically administered to patients who have had MI or patients with hypertension [ 18 ].…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…Indeed, microvascular blood flow is impaired in non-cardiac patients with subclinical hypothyroidism (Baycan et al, 2007). Recent rat studies from our group have shown that in hypertension (Carrillo-Sepulveda et al, 2019) and ischemic HF (Zhang et al, 2018), aortic rings are less responsive to the vasodilator acetylcholine. Pre-incubation with T3 largely restores vessel responsiveness toward normal.…”
Section: Additional Clinical Implicationsmentioning
confidence: 99%
“…Samples were then analyzed for vascular remodeling using Image J software according to established protocols (Gomez-Roso et al 2009 ; Maia et al 2014 ). Image J analysis included measures of aortic wall thickness, cross sectional area (CSA), wall thickness per lumen ratio (Wm/L), and lumen diameter, as previously described (Carrillo-Sepulveda et al 2019 ). Slides were digitized using an Olympus BX53 fluorescent microscope (Olympus America, Inc., Center Valley, MA, USA), high-resolution regular light digital images were captured under high-power magnifications (× 4) using an Olympus DP72 (Olympus America, Inc., Center Valley, MA, USA).…”
Section: Methodsmentioning
confidence: 99%